INCIDENCE OF MATURITY ONSET DIABETES OF THE YOUNG (MODY) AMONG THE SELECTED YOUNG ADULTS - V. LEELAVATHI (The Journal of Research ANGRAU, 2025)
This study investigated the incidence of maturity onset diabetes of the young (MODY) among young adults aged 18-35 years in Thoothukudi City, Tamil Nadu in the year 2021. Data was collected with the help of a well-structured interview schedule among 506 young adult participants. Four of the 506 participants, who met the MODY parameters (BMI below 30, two to three generations with diabetes, age below 35) were proceeded with additional genetic testing. Among the four, two were reported to have genetic mutations. One of the participants had a type 2 diabetes gene variation (AKT2 gene) and another had a MODY gene variation (KLF11 gene). Both Participants had a strong paternal side family history with diabetes and parents with diabetes. It indicates that having a strong family history of diabetes increases the likelihood that MODY and other kinds of diabetes will develop through heredity by some percent chance. The overall significance of this study is that it highlights the importance of early and accurate diagnosis for better treatment and management of this type of diabetes and also contributes to the spreading of knowledge on MODY